Lesion Characteristics of Chronic Totally Occluded Coronary Arteries on Computed Tomography Angiography in Patients with and without Prior Coronary Artery Bypass Graft - Arshad, Junaid; Siddique, Muhammad Bilal; Ahmed, Iftikhar; Sarwar, Naveed; Shehram, Muhammad; Abbas, Ali; Hassan, Faheem; Khan, Bakht Umar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To study the differences in characteristics of Chronic Totally Occluded coronary artery lesions on computed tomography angiography in patients with and without prior Coronary Artery Bypass Graft. Study Design: Comparative Cross-sectional Study. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Feb to Jul 2023. Methodology: The study included ninety six patients, with 48 patients in each group (prior CABG and non-CABG). Patients presenting with chest pain and having Chronic Totally Occluded lesions on Computed Tomography Angiography were selected using non-probability consecutive sampling. Data was analyzed using SPSS-23:00. Chi-square test was applied to find the association of lesion characteristics in study groups and level of significance was taken ˂0.05. Results: This study analyzed the characteristics of lesions in different target vessels among n= 96 patients, with 74(77.1%) being males and 22(22.9%) females. The mean age was 61.98±8.04 years. No statistically significant distinctions in the distribution of target vessels were observed when comparing the two groups. (p=0.48). However, osteal lesions had higher prevalence in the CABG group 20(41.7%) (p=0.04). The presence of blunt stump [21(43.8) vs 18(37.5); p=0.67] and calcification [(20(41.7%) vs 21(43.8%), p=1.00)] had no significant divergence between CABG and non-CABG groups. Bending was more common in the CABG group 17(35.4%) (p=0.002). In the CABG group, a higher occurrence of a side branch at the proximal cap 22(45.8%) (p=0.01) as well as a distal cap at the bifurcation 20(41.7%) (p<0.001), was noted. Conclusion: Chronic Totally Occluded lesions were more intricate ..